Density oscillations induced by individual ultracold two-body collisions - Guan, Qingze; Klinkhamer, Vincent M.; Klemt, Ralf; Becher, Jan Hendrik Willibald; Bergschneider, Andrea; Preiss, Philipp; Jochim, Selim; Blume, D. (Physical review letters, 2019)
Access to single-particle momenta provides new means of studying the dynamics of a few interacting particles. In a joint theoretical and experimental effort, we observe and analyze the effects of a finite number of ultracold two-body collisions on the relative and single-particle densities by quenching two ultracold atoms with an initial narrow wave packet into a wide trap with an inverted aspect ratio. The experimentally observed spatial oscillations of the relative density are reproduced by a parameter-free zero-range theory and interpreted in terms of cross-dimensional flux. We theoretically study the long-time dynamics and find that the system does not approach its thermodynamic limit. The setup can be viewed as an advanced particle collider that allows one to watch the collision process itself.
Gesehen am 08.04.2019